3-D Imaging of Cleat and Micro-cleat Characteristics, South Walker Creek Coals, Bowen Basin, Australia: Microfocus X-ray Computed Tomography Analysis - Asep Kurnia Permana (Geological Agency, 2012)
DOI: 10.17014/ijog.v7i1.131The Permian coals of the South Walker Creek area have a moderately to highly developed cleat system. The cleat fractures are well developed in both bright and dull bands, and generally parallel, inclined or perpendicular to the bedding planes of the seam, with the spaces open or filled by mineral matter, such as clay and carbonate minerals. Microfocus X-ray computed tomography (CT) technique was performed to identify cleat characteristics in the coal seams. This technique allows visualizing of microcleat distribution and mineralization in three dimensional images. Cleat mineralization in the coal seam occurs either as single mineral (monomineralic) or intermixed mineral (polymineralic) masses. The cross cutting relationship was shown by X-ray CT scan analysis. The timing of microcleat formation in the coal seam from early to late is carbonate minerals, clay minerals (kaolinite) plus minor high density (rutile or anatase) phases. Thus, a high resolution of microfocus X-ray CT does not only provides a better visualization, but also could identify microcleat orientation, cleat mineralization, and generation of microcleat.